2014
DOI: 10.1038/bjc.2014.173
|View full text |Cite
|
Sign up to set email alerts
|

Common infection-related conditions and risk of lymphoid malignancies in older individuals

Abstract: Background:Chronic antigenic stimulation may initiate non-Hodgkin (NHL) and Hodgkin lymphoma (HL) development. Antecedent, infection-related conditions have been associated, but evidence by lymphoproliferative subtype is limited.Methods:From the US SEER-Medicare database, 44 191 NHL, 1832 HL and 200 000 population-based controls, frequency-matched to all SEER cancer cases, were selected. Logistic regression models, adjusted for potential confounders, compared infection-related conditions in controls with HL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
(76 reference statements)
3
13
0
Order By: Relevance
“…The associations between HZ and hematological malignancies have been noted previously, including with CLL/SLL (30, 31), multiple myeloma (32, 33), lymphoplasmacytic lymphoma (14), and DLBCL (34). We observed that the associations for most of these malignancies were significant when zoster was assessed more than 3-5 years before cancer diagnosis/control selection.…”
Section: Discussionmentioning
confidence: 53%
“…The associations between HZ and hematological malignancies have been noted previously, including with CLL/SLL (30, 31), multiple myeloma (32, 33), lymphoplasmacytic lymphoma (14), and DLBCL (34). We observed that the associations for most of these malignancies were significant when zoster was assessed more than 3-5 years before cancer diagnosis/control selection.…”
Section: Discussionmentioning
confidence: 53%
“…However, concurrent diagnosis of TZL and gastrointestinal disease is not a common finding in our laboratory submissions nor based on prior literature. Prior studies have found no association of ulcerative colitis, inflammatory bowel disease, or gastroenteritis with NHL in humans, but the association may have been masked by using overall NHL instead of specific T‐cell subtypes. Certain long‐term gastrointestinal infections, including Helicobacter pylori and Campylobacter jejuni , have been associated with mucosa‐associated lymphoid tissue lymphomas in humans, highlighting the possibility that these may be subtype‐specific risk factors.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown asymptomatic bacteriuria may be present in 2%‐14% of dogs, which may suggest that diagnosed UTIs represent underlying chronic inflammation. One study evaluated UTIs (categorized as cystitis, prostatitis, and pyelonephritis) as a risk factor for non‐Hodgkin's lymphoma (NHL) in humans and found that prostatitis increased risk of overall NHL but not T‐cell NHL. This may be a novel association for TZL or may reflect differences in UTI etiology between people and dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic antigenic stimulation has been associated with increased risk of NHL development in humans, especially in older individuals . One study found that respiratory and skin infections in humans were linked with an increased risk of NHL, whereas gastrointestinal and urinary tract infections were not . Another study of 33 patients with rheumatoid arthritis demonstrated a shortened survival with lymphoma suggesting a more aggressive behaviour in cases with chronic inflammation .…”
Section: Discussionmentioning
confidence: 99%